ANALISIS KIMIA TANAH DAN REKOMENDASI PENINGKATAN KESUBURAN TANAH DI KEBUN PRAKTEK FAKULTAS PERTANIAN UNIVERSITAS NUSA NIPA - Fulgensius Sawan; Yovita Yasintha Bolly; Almaria Heliana (AGRICA, 2021)
Research on Analysis of Soil Chemical Content in the Practical Garden of the Faculty of Agriculture, University of Nusa Nipa, East Alok District, Sikka Regency has been carried out from October to December 2021. This study aims to determine the chemical content of the soil in the Practical Garden of the Faculty of Agriculture, University of Nusa Nipa, East Alok District, Sikka Regency. . The research method used is observation, laboratory testing, and literature study. Analysis of soil chemical content using a dry soil test device with a diagonal composite soil sampling method. The results showed that the soil in the practice garden had low organic C content (1.00-2.00%), neutral pH (6.5-7.5), high phosphorus content (26-35), and also Potassium content is in the moderate to low range.